228k views
2 votes
The graph shows the function f(x)=−12x+26 and g(x)=−(15)−x+2+3 .

What are the solutions of the equation −12x+26=−(15)−x+2+3 ?

User Yer
by
6.0k points

2 Answers

3 votes

Answer:

x=2 and 4

Explanation:

User Dave Cole
by
4.6k points
1 vote

Answer:

x=36/11=3.2727...

Explanation:

The solution can be found by solving for x.

First, combine like terms and simplify each side of the equation.


-12x+26 = -(15)-x+2+3\\-12x+26 = -15-x+5\\-12x+26=-10-x

Second, use inverse operations to move terms across the equal sign.


-12x+26 = -10-x\\-12x+x+26=-10-x+x\\-11x+26=-10\\-11x+26-26=-10-26\\-11x=-36\\x=36/11=3.2727...


User Shivayan Mukherjee
by
5.3k points